2013
DOI: 10.1371/journal.pone.0075905
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain, a Cardiac Glycoside, Inhibits the Fanconi Anemia/BRCA Pathway Activated by DNA Interstrand Cross-Linking Agents

Abstract: Modulation of the DNA repair pathway is an emerging target for the development of anticancer drugs. DNA interstrand cross-links (ICLs), one of the most severe forms of DNA damage caused by anticancer drugs such as cisplatin and mitomycin C (MMC), activates the Fanconi anemia (FA)/BRCA DNA repair pathway. Inhibition of the FA/BRCA pathway can enhance the cytotoxic effects of ICL-inducing anticancer drugs and can reduce anticancer drug resistance. To find FA/BRCA pathway inhibitory small molecules, we establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…To date, four separate FAPi have been described that are commercially available; curcumin, its monoketone analogues EF-24 & 4H-TTD, and the menadione analogue DDN [13-16]. However, in initial toxicity studies, we found that 4H-TTD was toxic to both U87 and U138 cells even at nM concentrations (data not shown), and was therefore excluded from our further analyses, as was the recently reported FAPi Ouabain [24]. …”
Section: Resultsmentioning
confidence: 91%
“…To date, four separate FAPi have been described that are commercially available; curcumin, its monoketone analogues EF-24 & 4H-TTD, and the menadione analogue DDN [13-16]. However, in initial toxicity studies, we found that 4H-TTD was toxic to both U87 and U138 cells even at nM concentrations (data not shown), and was therefore excluded from our further analyses, as was the recently reported FAPi Ouabain [24]. …”
Section: Resultsmentioning
confidence: 91%
“…Accordingly, the fact that within 24 h, OU and Digo reduce the expression of the proteasome subunit genes, while within 8 h they induce the activation of the proteasome enzymatic activities, leads us to speculate that cells activate a rapid compensatory mechanism to buffer the CGs-dependent proteasome activation. Interestingly, the ability of OU to activate the proteasome can also explain some of the previously reported effects of this CG on specific components of the ubiquitination pathway [ 52 ].…”
Section: Discussionmentioning
confidence: 93%
“…Cardiac glycosides also affect several pathways central for tumor formation. Digoxin was shown to: suppress growth of hypoxic NSCLC and breast cancer cells (2) (3) (4) and possibly decrease the risk for castrate resistant prostate cancer through inhibition of hypoxia inducible factor 1 (5, 6); reduce protein synthesis of the tumor suppressor gene P53 through the Src/MAPK pathway (7); inhibit the FA/BRCA pathway (8); induce autophagy through mTOR and ERK1/2 signaling pathways in NSCLC cells (9) (10); and induce immunogenic cell death in immune-competent but not immune-deficient mice through inhibition of the Na+/K+-ATPase (11). Furthermore, the alpha 1 isoform of the sodium potassium ATPase mediates cell migration and growth in addition to the pumping activities and is down regulated in colon, pancreas, kidney, bladder and prostate cancers (12, 13).…”
Section: Introductionmentioning
confidence: 99%